Chronic abdominal pain. A multidisciplinary approach in gastroenterology and psychiatry - O.Yu. Gubska (Gastroenterologìa)
Background. Chronic abdominal pain syndrome is one of the manifestations of gut-brain interaction disorders, which occupy a significant place among gastrointestinal pathologies, but remain insufficiently recognized in clinical practice. Centrally mediated abdominal pain syndrome (CAPS) is singled out as a specific manifestation of this disorder in modern literature. This disease encompasses a range of gastrointestinal and extra-gastrointestinal symptoms and is closely associated with psychological distress, neurological and psychiatric disorders. Given an increase in stress factors in the modern world and the constant distress of wartime in Ukraine, the diagnosis of CAPS requires from clinicians an understanding of the relationship between the central nervous system and gastrointestinal diseases at each link of the health care system. Purpose: to review publications on the pathogenesis, general principles of diagnosis and treatment of CAPS as an independent nosology in the category of the gut-brain axis disorders (GBAD), as well as to draw attention to the need for a comprehensive psychosomatic approach to the management of patients with this disease. Materials and methods. A search was made for articles covering functional gastrointestinal disorders and chronic abdominal pain in domestic and foreign publications. Twenty-five works were used for the period from 1982 to 2024. Among them, 8 % were published in Ukraine, and 92 % — abroad. The publications considered the following topics: chronic abdominal pain as such — 13 articles, diagnosis of functional disorders in the context of surgery — 3 articles, psychosomatic influence on gastrointestinal pathologies — 3 articles, neuromodulation pharmacotherapy — 2 articles, communication and psychotherapeutic strategies in the management of patients with GBAD — 4 articles. Discussion. The development of CAPS is caused by central sensitization. Due to the need to exclude organic pathology and in a long-term observation of the patient, as well as due to the association of the diagnosis with mental pathologies, a critical factor is a thorough history collection, focusing on the description of pain. Antidepressants are the basis of pharmacological therapy for CAPS, with tricyclic antidepressants play a leading role due to their pronounced analgesic effect in low doses, but selective serotonin reuptake inhibitors and serotonin-norepinephrine reuptake inhibitors are also important as the drugs of choice in patients with chronic pain and depressive states. The effectiveness of drug treatment is enhanced in comprehensive therapy and combination with psychotherapeutic intervention methods, which should be offered to patients as early as possible. Conclusions. CAPS as a representative of the GBAD group is a gastrointestinal pain disorder with a central determinant. Due to the growing clinical prevalence and complexity of this group of diseases, there is an urgent need for a comprehensive approach to their management based on the modern biopsychosocial model. The choice of therapy should include all the features of the occurrence and course of the disease, and psychopharmacological agents and psychotherapeutic interventions chosen should be justified and effective.